(untitled) (MAUSAM, 1966)
A pilot scheme to study the mesoscale structure of the summer thunder storms in Delhi area and their effect on the surface weather was put into operation during the months of June, July and August 1961, A network of seven stations with autographic charts was established round Delhi, Some interesting results on surface squalls and pressure and temperature changes associated with the thunderstorms were obtained from this study and are presented.